PROBLEMATIKA SELF DECLARE PRODUK MAKANAN DAN MINUMAN PELAKU USAHA MIKRO DI INDONESIA - ashibly, Ashibly (Faculty of Law, Universitas Tanjungpura, 2025)
Abstract The self declare scheme in Indonesia, especially applied to micro and small business actors (MSEs), is a form of government support for micro and small business actors (MSEs) in the context of halal certification. However, behind it, there are several problems that are serious challenges such as low awareness of business actors registering their products to obtain halal certificates through the self declare scheme, data falsification, misuse of halal certification, changes in raw materials and non-compliance with the established halal standards. This study aims to analyze the problems of the self declare scheme for business actors by focusing on the problems of the self declare scheme linked to aspects of Islamic values and business ethics of business actors (tazkiyah business theory). The type of research in this paper uses normative legal research type. While the approach in this study uses an approach from views and doctrines. The results of the study found that behind the ease of the self declare scheme, there are problems that occur such as low awareness of micro business actors to register their products. Misuse of halal certificates by manipulating halal certification application data such as the example of a fruit juice product case with the Nabidz trademark. Violations in the production process such as the use of additives that do not have halal certification. Violations of product raw materials, Using names of objects or animals that are prohibited. Potential changes in materials, In the context of self declare, the theory of tazkiyah business and halal certification shows a mutually reinforcing relationship. The principles of tazkiyah, which emphasize honesty, compliance, and accountability, are in accordance with the objectives of halal certification in providing assurance regarding product purity. Abstrak Skema self declare (pernyataan mandiri) di Indonesia, khususnya yang diterapkan kepada pelaku usaha mikro dan kecil (UMK) merupakan bentuk keberpihakan pemerintah kepada pelaku usaha mikro dan kecil (UMK) dalam konteks sertifikasi halal, Namun, di balik itu, terdapat sejumlah permasalahan yang menjadi tantangan serius seperti rendahnya kesadaran pelaku usaha untuk mendaftarkan produknya untuk mendapatkan sertifikat halal melalui skema self declare, pemalsuan data, penyalahgunaan sertifikasi halal, perubahan bahan baku dan ketidakpatuhan terhadap standar halal yang ditetapkan. penelitian ini bertujuan untuk menganalisis mengenai problematika skema self declare bagi pelaku usaha dengan fokus pada permasalahan skema self declare dikaitkan pada aspek nilai-nilai islam dan etika bisnis pelaku usaha (teori bisnis tazkiyah). Jenis penelitian dalam tulisan ini menggunakan jenis penelitian penelitian hukum normatif. Sedangkan pendekatan dalam penelitian ini menggunakan pendekatan dari pandangan-pandangan dan doktrin-doktrin. Hasil penelitian ditemukan bahwa dibalik kemudahan skema self declare, tersimpan problematika yang terjadi seperti rendahnya kesadaran pelaku usaha mikro untuk mendaftarkan produknya. Penyalahgunaan sertifikat halal dengan memanipulasi data pengajuan sertifikasi halal seperti contoh kasus produk jus buah dengan merek dagang Nabidz. Pelanggaran dalam proses produksi seperti penggunaan bahan aditif yang tidak memiliki sertifikasi halal. Pelanggaran terhadap bahan baku produk, Menggunakan nama yang benda atau hewan yang diharamkan. Potensi perubahan bahan, Dalam konteks self declare, teori bisnis tazkiyah dan sertifikasi halal menunjukkan hubungan yang saling memperkuat. Prinsip-prinsip tazkiyah, yang menggarisbawahi kejujuran, kepatuhan, dan akuntabilitas, kesesuaian dengan tujuan sertifikasi halal dalam memberikan jaminan mengenai kemurnian produk.